Histamine H3 Receptor Signaling Regulates the NLRP3 Inflammasome Activation in C2C12 Myocyte During Myogenic Differentiation - Chen, Yan; Ma, Yuan; Feng, Jin Jin; Wang, Yi He; Li, Tian Fang; Nurmi, Katariina; Eklund, Kari K.; Wen, Jian Guo (Frontiers in Pharmacology, 2021)
NLRP3 inflammasome has been implicated in impaired post-injury muscle healing and in muscle atrophy. Histamine receptors play important role in inflammation, but the role of histamine H3 receptor (H3R) in myocyte regeneration and in the regulation of NLRP3 inflammasome is not known. We studied the effects of H3R signaling on C2C12 myocytes viability, apoptosis and tumor necrosis factor alpha (TNFα)-induced NLRP3 inflammasome activation during striated myogenic differentiation at three differentiation timepoints (days 0, 3 and 6). Expression of Nlrp3, interleukin-1β (IL-1β), and myogenesis markers were determined. TNFα reduced overall viability of C2C12 cells, and exposure of the cells to TNFα induced apoptosis cells at D6. Activation of H3 receptor had no effect on viability or apoptosis, whereas inhibition of H3R increased TNFα-induced apoptosis. Stimulation of the C2C12 cells with TNFα increased Nlrp3 mRNA expression at D3 and D6. Moreover, TNFα reduced the expression of myogenesis markers MyoD1, Myogenin, and Myosin-2 at D3 and D6. H3R attenuated TNFα-induced expression of Nlrp3 and further inhibited the myogenesis markers expression; while H3R -blockage enhanced the proinflammatory effects of TNFα and increased the myogenesis marker expression. TNFα-induced secretion of mature IL-1β was dependent on the activation of the NLRP3 inflammasome, as shown by the reduced secretion of mature IL-1β upon treatment of the cells with the small molecule inhibitor of the NLRP3 inflammasome (MCC950). The activation of H3R reduced the TNFα-induced IL-1β secretion, while the H3R blockage had an opposite effect. In conclusion, the modulation of H3R activity regulates the effects of TNFα on C2C12 myocyte differentiation and TNFα-induced activation of NLRP3 inflammasome. Thus, H3R signaling may represent a novel target for limiting postinjury muscle inflammation and muscle atrophy.